THE USE OF AN ONLINE LEARNING SITE ‘RANDALL’S ESL’ IN TEACHING LISTENING (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Learning a language, especially English is of the utmost importance because it is not only a widely-spoken tongue but also one that could assist students in their future careers. However, some students in Indonesia continue to believe that learning English is difficult. There are four fundamental abilities they must master. They are engaged in listening, speaking, reading, and writing activities. In this study, the authors intend to demonstrate how Randall's ESL website could be used as one of the options for teachers and students to improve their English listening skills. The authors utilized a qualitative methodology, and the dataset was obtained from the official "Randall's ESL" website. The writers used Alexander Fedorov's Media Education philosophy. The authors also drew data from other sources, such as journal articles and conference proceedings, to support the research. This study revealed that "Randall's ESL" was one of the most successful options for enhancing students' listening skills and teachers' instructional practices.
Keywords: listening skill; media education; teaching